CONTRASTIVE ANALYSES OF ENGLISH AND UZBEK IT TERMINOLOGY - Norqobilova , Feruza Abdig‘affor qizi (Educational Research in Universal Sciences, 2023)
This paper presents a contrastive analysis of IT terminology in English and Uzbek. The study aims to identify the similarities and differences between the two languages in terms of their IT vocabulary. The research methodology involved corpus analysis of IT texts in both languages. The findings reveal that both English and Uzbek languages have adopted and integrated foreign IT terms into their vocabulary. However, there are also notable differences in terms of the frequency of use, semantic range, and linguistic features of IT terms. The results of this study can be useful for language learners, translators, and IT professionals working in cross-cultural contexts.